2021
DOI: 10.1016/j.diabres.2021.108699
|View full text |Cite
|
Sign up to set email alerts
|

Targeted lipidomics reveals associations between serum sphingolipids and insulin sensitivity measured by the hyperinsulinemic-euglycemic clamp

Abstract: Background SPs are a group of ubiquitously produced lipids that are structurally involved in cell membranes and include SMs, ceramides, GM3s, etc. Sphingolipids and their substrates and constituents, FAs, are implicated in the pathogenesis of various metabolic diseases associated with obesity, diabetes, and atherosclerosis. Decreased insulin sensitivity or insulin secretion is a multifactorial condition related to obesity and diabetes. Therefore, it is likely that perturbations in serum SPs are associated with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Because sphingolipid decomposition metabolism might stimulate the effect of insulin signal transmission ( 38 ). In addition, Ye J et al have found that serum sphingolipids of SM/Cer and SM d18:0/26:0 associated with insulin sensitivity ( 39 ), and serum sphingolipids of hexose ceramide were determined the significant correlation with T2DM ( 40 ). Furthermore, tryptophan, an essential nutrient in mammals, has a variety of functions, such as maintaining immune homeostasis ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because sphingolipid decomposition metabolism might stimulate the effect of insulin signal transmission ( 38 ). In addition, Ye J et al have found that serum sphingolipids of SM/Cer and SM d18:0/26:0 associated with insulin sensitivity ( 39 ), and serum sphingolipids of hexose ceramide were determined the significant correlation with T2DM ( 40 ). Furthermore, tryptophan, an essential nutrient in mammals, has a variety of functions, such as maintaining immune homeostasis ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data were derived from a cohort of participants who had undergone both hyperinsulinemic-euglycemic clamp and lipidomic analysis in the First Affiliated Hospital of Nanjing Medical University, Nanjing, China [ 17 ]. The participants who underwent the hyperinsulinemic-euglycemic clamp had not taken any medication or supplement, had no history of smoking or high alcohol intake (four or more standard drinks per week for men and two or more standard drinks per week for women), severe disease, acute inflammation or pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…The hyperinsulinemic-euglycemic clamp method established by DeFronzo et al was used to assess whole-body insulin sensitivity [ 20 ]. The specific clamp test details were described previously [ 17 ]. The hepatic glucose production could be suppressed by a high dose of insulin use (> 80 mU/m2*min).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, 500 μl supernatant was vacuum centrifuged to dryness. The mass spectra and bioinformatics analyses were determined as previously described (Ye et al, 2021).…”
Section: Experimental Designmentioning
confidence: 99%